A study of gross congenital malformation at birth - Gandhi, Pooja R.; Vora, Hetal D.; Vasavada, Halak J.; Patelia, Mehul T.; Popatiya, Pragneshkumar L.; Vora, Naznin (International Journal of Contemporary Pediatrics, 2019)
Background: A congenital anomaly is a structural anomaly of any type that is present at birth. Congenital anomalies may be induced by genetic or environmental factors. Most congenital anomalies, however, show the familial patterns expected of multi-factorial inheritance. The aims and objective of this study were to study the incidence of visible congenital malformations at birth, to study risk factors, to find associated internal malformations. Methods: It is a retrospective cross-sectional study carried out in a tertiary care hospital affiliated to a medical college. The Inclusion criteria include all new-borns delivered in the hospital with visible congenital malformations examined within 48 hours of birth. Extramural babies were included if they had presented within 48 hours after birth. The Exclusion criteria include still births were excluded from the study. Results: Percentage of congenital malformation was 1.32%. Most common systems involved were musculoskeletal system (46.34%) followed by genitourinary system (21.34%) and gastrointestinal system (14.02%). Conclusions: All Babies with gross congenital malformation should be screened for internal malformation. The incidence of CNS malformation has reduced than observed in previous studies which suggest awareness about antenatal folic acid supplementation. Other than CNS anomalies, other system anomalies were not diagnosed antenatally despite antenatal ultrasound being done in maximum number of mothers, which suggest use of 3D or 4D scan antenatally.